A Comparative Analysis of UTAUT and UTAUT 2 in M-Commerce and M-Banking - Ginting, Tri Wulandari; Sinaga, Joy Nasten (Universitas Nusantara PGRI Kediri, 2025)
Background: The debate over the superiority between UTAUT and UTAUT 2 has driven the development of UTAUT 3. However, this latest model is still not the best solution, as several variables remain less influential. Objective: This study aims to determine which UTAUT model is superior in technology acceptance, particularly for m-commerce and m-banking. Methods: Multiple linear regression was used to determine the direction and magnitude of the influence of independent variables on the dependent variable, analyzing key factors affecting the adoption of mobile banking and m-commerce by comparing UTAUT and UTAUT 2. Results: In m-commerce, UTAUT highlights behavioral intention and facilitating conditions, while UTAUT 2 adds habit and price value as key influencing factors. Conclusion: For m-banking, both models are equally effective, but UTAUT 2 is superior due to the strong influence of habit. In m-commerce, UTAUT 2 is also preferable, as price value significantly affects behavioral intention.